Priorities for Fighting Serious Transnational Crime - Between the EU's Financial Protection Mechanism and Good Practices in Shared Management - Florin Tudor; Simona Petrina Gavrilă; Gabriela Getty Popescu (Communications of International Proceedings, 2021)
The approach of OLAF's investigations into suspected fraud reveals that national authorities often delay administrative review and possible criminal investigation, often reducing the chances of prosecuting perpetrators who commit acts that seriously affect the EU budget, with the often intervention of the statute of limitation in benefit of perpetrators. The causes are many, but the obvious differences in the legislative approach in the Member States are certainly the most important challenge for the authorities. Although the establishment of the European Public Prosecutor's Office is, in our opinion, the right decision to investigate such serious transnational crime, we believe that its current rules of procedure will create a possible crisis because, in many cases, it is not correlated with shared management with the Member States resulting from the Treaty. The present study aims at an x-ray of the main reasons that led to such a condition, but also to highlight the legislative overlaps in the mentioned field of investigation and, last but not least, to propose constructive solutions to unblock the investigation that new European Public Prosecutor's Office will begin.
Keywords: Crime; administrative investigations; financial interests; transnational crime; tax competition; transparency